TITLE: DEVELOPING EFFECTIVE RISK MANAGEMENT STRATEGIES FOR FOREIGN INVESTMENT PROJECTS IN UZBEKISTAN (World Economics and Finance Bulletin, 2023)
Foreign investment in Uzbekistan has increased significantly in recent years, thanks to the country's economic and political reforms, which have created a more favorable environment for foreign investors. However, investing in Uzbekistan is not without risk. Political instability, corruption, and regulatory hurdles can all pose challenges for foreign investors. To mitigate these risks, it's essential to develop effective risk management strategies
Keywords: Foreign investment; risk management strategies; Uzbekistan